2015
DOI: 10.1186/s12986-015-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Red peppers with moderate and severe pungency prevent the memory deficit and hepatic insulin resistance in diabetic rats with Alzheimer’s disease

Abstract: BackgroundDementia induced by β-amyloid accumulation impairs peripheral glucose homeostasis, but red pepper extract improves glucose homeostasis. We therefore evaluated whether long-term oral consumption of different red pepper extracts improves cognitive dysfunction and glucose homeostasis in type 2 diabetic rats with β-amyloid-induced dementia.MethodsMale diabetic rats received hippocampal CA1 infusions of β-amyloid (25–35) (AD) or β-amyloid (35–25, non-plaque forming), at a rate of 3.6 nmol/day for 14 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In our present study, deficiency of brain impaired insulin signaling pathway was found in the brain of T2D rats, which is consistent with our previous findings that showing impaired brain insulin signaling pathway in individuals with type 2 diabetes [ 9 , 12 ]. Proteins involved in insulin signaling pathway was up-regulated in T2D+CAP group compared to T2D rats, which is also consistent with a recent study showed that the administration of extracts of red peppers restored insulin signaling pathway and prevented tau hyperphosphorylation and β-amyloid accumulation in a rat model of T2D combined with β-amyloid-induced dementia [ 43 ]. Studies suggested that calcium influx triggered PI3K/AKT signaling pathway in several tissues [ 44 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our present study, deficiency of brain impaired insulin signaling pathway was found in the brain of T2D rats, which is consistent with our previous findings that showing impaired brain insulin signaling pathway in individuals with type 2 diabetes [ 9 , 12 ]. Proteins involved in insulin signaling pathway was up-regulated in T2D+CAP group compared to T2D rats, which is also consistent with a recent study showed that the administration of extracts of red peppers restored insulin signaling pathway and prevented tau hyperphosphorylation and β-amyloid accumulation in a rat model of T2D combined with β-amyloid-induced dementia [ 43 ]. Studies suggested that calcium influx triggered PI3K/AKT signaling pathway in several tissues [ 44 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…Behavioral alterations were monitored after 2 weeks from the STZ infusion (versus the negative controls in group I) using passive avoidance (short-term memory) [64] and Morris water maze (MWM) (spatial memory) tests [50] to examine for the development of Alzheimer's model. Rats with retention latency less than 300 s were studied by further subdivision of rats into 2 groups as follows: STZ-induced AD, capsaicin untreated group, where ten rats were treated by intragastric infusion of the vehicle (0.9% saline) for 47 days, served as positive controls (group II); STZ-induced AD, capsaicin treated group, where ten rats were treated with capsaicin, 10 mg/kg BW in 0.2 ml saline, and 0.1% ethanol by intragastric infusion for 47 days (group III) [30,78]. Flow chart and the experimental design are shown in Fig.…”
Section: Biological Study Experimental Designmentioning
confidence: 99%
“…Curcumin activates HSF1 (Teiten et al 2009) and augments memory function (Zhang et al 2015a). Capsaicin activates calcium channels (TRPV) and thereby activates HSF1 (Bromberg et al 2013) and improves cognitive function while blocking tau phosphorylation and β-amyloid accumulation in a diabetic-dementia animal model (Yang et al 2015).…”
Section: Hsf1 Inducers and Cognitive Preservationmentioning
confidence: 99%